2005
DOI: 10.1902/jop.2005.76.10.1654
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Three Oral Sprays on Plaque and Gingival Inflammation

Abstract: These results indicate that both CHX and CHX/B-HCl sprays have equal clinical effectiveness, but only B-HCl spray has less anti-plaque and anti-gingivitis effects. Furthermore, CHX/B-HCl spray causes more side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 39 publications
(68 reference statements)
0
13
1
3
Order By: Relevance
“…Another side effect of chlorhexidine discussed in the literature is brownish staining of the teeth. However, in the present study only two cases showed these characteristics, i.e., 15% reported small areas of staining that appeared after 30 days of using the spray, which was removed easily by dental prophylaxis …”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Another side effect of chlorhexidine discussed in the literature is brownish staining of the teeth. However, in the present study only two cases showed these characteristics, i.e., 15% reported small areas of staining that appeared after 30 days of using the spray, which was removed easily by dental prophylaxis …”
Section: Discussioncontrasting
confidence: 67%
“…Many researchers still report that a major side effect of chlorhexidine is its bitter taste, which means that treatment has to be restricted to short periods, which often leads to abandonment . The authors also evaluated at intervals of 7, 14, 30, and 60 days to monitor the progress of spray applications and to determine whether there were complications resulting from staining and taste alterations, which might cause the patient to interrupt the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chlorhexidine has been accepted as the golden standard in clinical research studies. 30,31 That is why we also compared an antibacterial toothpaste by switching with chlorhexidine which has already been accepted as a golden standard antibacterial agent. In the third group, subjects brushed for 3 minutes, with a commonly used toothpaste (Ipana Ⓡ Procter & Gamble, Istanbul, Turkey) which possessed no antibacterial activity other than that provided by 0.32% sodium fluoride only, while the fourth group patients brushed with an antimicrobial toothpaste (One Drop Only Ⓡ , One Drop Only Gmbh, Berlin, Germany), which included tea tree oil (0.37%), peppermint oil (2.6%), clove oil (concentration not disclosed by the manufacturer) and bisabolol (0.35%).…”
Section: Methodsmentioning
confidence: 99%
“…Os métodos mecânicos para limpeza dentária devem ser a escolha antes da utilização de qualquer tipo de agente químico para o controle rotineiro do biofilme dentário. O controle químico do biofilme dentário deverá ser empregado de forma suplementar, quando o controle mecânico, no sentido de evitar o acúmulo de bactérias sobre os dentes, não puder ser realizado diariamente ou estiver inadequado (ANDERSON, 2003;BOZKURT et al, 2005;PARASKEVAS, 2005;LAING et al, 2008).…”
Section: Introductionunclassified